COLLABORATIVE GOVERNANCE DALAM MELINDUNGI HUTAN LINDUNG BUKIT BETABUH DI KECAMATAN KUANTAN MUDIK KABUPATEN KUANTAN SINGINGI TAHUN 2019 - Nolarian, Enci; ", Adlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Collaborative Governance In Protecting Protected Forests by forming a forest farmer group in Kuantan Mudik District, there are several forest farmer groups. And its existence has been guaranteed in the local village head's decree. This study aims to find out how Collaborative Governance in Protecting the Bukit Betabuh Protected Forest in Kuantan Mudik District, Kuantan Singingi Regency, then also to determine the Collaborative Governance Process in Protecting the Bukit Betabuh Protected Forest in Kuantan Mudik District, Kuantan Singingi Regency. The location of the research was carried out at UPT KPH Singingi and in Air Buluh Village, Kuantan Mudik District, Kuantan Singingi Regency. Furthermore, data collection techniques were carried out by interviews, documentation and library studies.The results of this study are Collaborative Governance in Protecting the Bukit Betabuh Protected Forest in Kuantan Mudik District, Kuantan Singingi Regency which is carried out to establish forest farmer groups through face-to-face dialogue between farmer groups and extension agents as an effort to protect the forest. The establishment of Forest Farmers Groups in Kuantan Mudik Sub-district has not been optimal. This is caused by several factors, such as the lack of Stakeholder cooperation and financial resources and also not all of the forest farmer groups as a whole have been formed. Keywords: Collaborative Governance, Protecting, Protected Forest